Sistem Penandaan Pada Makanan Jajanan Tradisional Sunda - Hertin Badriah (Calakan : Jurnal Sastra, Bahasa, dan Budaya, 2024)
This reseacrh aims at describing sign system in Sundanese snack traditional food. The sign system describes signifier and signified in snack food of kiripik, combro, misro, katimus, colenak, sukro, sampe goreng, and cilok. Signifier refers to food name dan signified relates to food concept. Research method applied qualitative descriptive by using data collection technique of active observation and in-depth interview. The data taken from Sundanese snack traditional food. The result research shows food sign system cannot be separated from signifier that explains form and signified explains concept or Sundanese traditional food meaning. Naming of snack food has arbitrary or non-arbitrary system. Arbitrary means signifier is created randomly and non-arbitrary, signified is created associatively